Sowing the seeds of food security - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The Role of Smallholder Farmers in Seed Production Systems. Report and Recommendations of a Study Visit, Zimbabwe, 1999. CTA. 2000. 100 pp. ISBN 92 9081 2176. CTA number 965. 10 credit points.